Four‐dimensional imaging of moisture dynamics during landslide reactivation. Issue 1 (25th January 2017) - Uhlemann, Sebastian; Chambers, Jonathan; Wilkinson, Paul; Maurer, Hansruedi; Merritt, Andrew; Meldrum, Philip; Kuras, Oliver; Gunn, David; Smith, Alister; Dijkstra, Tom
Abstract: Landslides pose significant risks to communities and infrastructure, and mitigating these risks relies on understanding landslide causes and triggering processes. It has been shown that geophysical surveys can significantly contribute to the characterization of unstable slopes. However, hydrological processes can be temporally and spatially heterogeneous, requiring their related properties to be monitored over time. Geoelectrical monitoring can provide temporal and volumetric distributions of electrical resistivity, which are directly related to moisture content. To date, studies demonstrating this capability have been restricted to 2‐D sections, which are insufficient to capture the full degree of spatial heterogeneity. This study is the first to employ 4‐D (i.e., 3‐D time lapse) resistivity imaging on an active landslide, providing long‐term data (3 years) highlighting the evolution of moisture content prior to landslide reactivation and showing its decline post reactivation. Crucially, the time‐lapse inversion methodology employed here incorporates movements of the electrodes on the unstable surface. Although seasonal characteristics dominate the shallow moisture dynamics during the first 2 years with surficial drying in summer and wetting in winter, in the months preceding reactivation, moisture content increased by more than 45% throughout the slope. This is in agreement with independent data showing a significant rise in piezometric heads and shallow soil moisture contents as a result of prolonged and intense rainfall. Based on these results, remediation measures could be designed and early‐warning systems implemented. Thus, resistivity monitoring that can allow for moving electrodes provides a new means for the effective mitigation of landslide risk. Key Points: Spatial and temporal variations of subsurface moisture content shown by long‐term resistivity monitoring Long‐term resistivity monitoring study implementing electrode movements on an active landslide Field validation of the impact of elevated pore pressures and preferential flow on slope stability